(untitled) (Revista Angelus Novus, 2011)
In 2002, the students of Faculdade de Filosofia Letras e Ciências Humanas of Universidade de São Paulo remained on strike for 108 days demanding the contract of 259 professors and the automatic reposition of the teaching body. During this movement many documents were produced. A portion of these constitute the Acervo Documental da Greve Estudantil de 2002 da FFLCH-USP. This article intends to describe the process of gathering, organizing, conditioning, registering, digitalization and data bank production of these documents.